The Role of SKP Application In Improving Employee Performance - Febrian Jaya, Aldi; Fadillah, Alfandi; Khumayah , Siti; Imawan , Khaerudin (Journal Research of Social Science, Economics, and Management, 2024)
Civil Servants (PNS) are in front of all government activities to meet the needs of the community and become the driving force of government processes in Indonesia. The government’s human resources agency (BKPSDM) in Majalengka Regency has started carrying out their work procedures online as everyone can now access the Internet. processes and obstacles and how to overcome these obstacles This study uses qualitative research with descriptive methods, the selection of this method is in accordance with the opinions of Miles and Huberman Punch (1992), namely data reduction, data presentation and conclusions. Data was collected from various sources through interviews. Observations were also made at the place of Employee Performance Target (SKP). Based on the results of the study, it can be concluded that the SKP assessment at the Human Resources Personnel and Development Agency (BKPSDM) of Majalengka Regency performance standards assessed and evaluated by the sirancage system are considered quite effective. This is because for filling out SKP related to online attendance with the sirancage application itself, this ASN management independently has the ability to describe and identify ASNs that function effectively and not. ASN itself uses SKP components and work behavior.